Arabidopsis thaliana TCP15 interacts with the MIXTA-like transcription factor MYB106/NOECK - Camoirano, Alejandra (2021)
MYB106 and MYB16 are MIXTA-like transcription factors that control trichome maturation and cuticle formation in Arabidopsis. In a recent study, we found that the TEOSINTE BRANCHED 1, CYCLOIDEA and PROLIFERATING CELL FACTORS (TCP) transcription factor TCP15 also acts as an important regulator of aerial epidermis specialization in Arabidopsis through the control of trichome development and cuticle formation. TCP15 and MYB106 regulate the expression of common groups of genes, including genes coding for transcription factors and enzymes of the cuticle biosynthesis pathway. In this study, we report that TCP15 physically interacts with MYB106 when both proteins are expressed in yeast cells or Nicotiana bentamiana leaves. Furthermore, we also observed interaction in leaves of Arabidopsis thaliana. Altogether, our findings raise the possibility that TCP15 and MYB106 bind together to the promoters of target genes to exert their action. Our data provide a base to investigate the role of TCP-MIXTA complexes in the context of cuticle development in Arabidopsis thaliana.